2021
DOI: 10.3389/fpsyg.2021.602023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Expressive Brand and Susceptibility to Interpersonal Influence on Brand Addiction: Mediating Role of Brand Passion

Abstract: Although the concept of the consumer–brand relationship has undergone rapid change over the past two decades, the issue of brand addiction is still generally neglected in the literature. Based on social identity theory, the research develops a conceptual model of the influence of self-expressive brands (SEBs) and susceptibility to interpersonal influence (SUSCEP) on brand addiction. The results of this research demonstrate both separate and joint effects of SEBs and SUSCEP on brand addiction. In addition, harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 50 publications
(85 reference statements)
2
14
0
Order By: Relevance
“…The few empirical studies that have been conducted on brand addiction have identified social comparison and materialism (Le, 2020) and brand self-expressiveness, brand innovativeness and brand authenticity as influences on brand addiction (Francioni et al , 2020). Most recently, Bai et al (2021) found that brand passion, a component of brand love, directly influences brand addiction. Likewise, Le (2020, p. 1) argued that brand addiction “refers to consumers' addictive behavior, with consumers particularly loving the brand,” finding it associated with being a more intense but unhealthier relationship with a brand.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The few empirical studies that have been conducted on brand addiction have identified social comparison and materialism (Le, 2020) and brand self-expressiveness, brand innovativeness and brand authenticity as influences on brand addiction (Francioni et al , 2020). Most recently, Bai et al (2021) found that brand passion, a component of brand love, directly influences brand addiction. Likewise, Le (2020, p. 1) argued that brand addiction “refers to consumers' addictive behavior, with consumers particularly loving the brand,” finding it associated with being a more intense but unhealthier relationship with a brand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first to introduce the concept of brand addiction were Mrad andCui (2016, 2017). The literature on brand addiction is still nascent, and researchers are mostly focused on its conceptualization and operationalization (Bai et al, 2021). In fact: [.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers become emotionally connected to the brand as the brand carries the meaning of their idols. Therefore, companies that integrate idols into their brands can stimulate the emotional migration of fan consumers ( Ilicic and Webster, 2014 ), enhance their recognition of the brand and its emotional value, and kindle positive emotions ( Bai et al, 2021 ). The perceived emotional value of the brand interacts with the consumer’s brand experience to ultimately produce brand passion.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Interpersonal influence is a type of social influence of group members that encourages or forces others to confirm the group's values. The other two types of social influence are normative and informative (Bai, Yin, Yu, Wei, & Wu, 2021). From a marketing perspective, interpersonal influence is important to increasing purchase intention and brand reputation.…”
Section: Interpersonal Influencementioning
confidence: 99%
“…Interpersonal influence is a component related to society that significantly impacts consumer decision-making and the adoption of new technologies (D'Rozario & Choudhury, 2000). Numerous research has demonstrated that when customers are open to interpersonal influence, brand advocacy may become the most effective source of information (Bai et al, 2021).…”
Section: Interpersonal Influence and Brand Advocacymentioning
confidence: 99%